Metabolism, Mitochondrial Dysfunction, and Redox Homeostasis in Pulmonary Hypertension - Daniel Colon Hidalgo; Hanan Elajaili; Hagir Suliman; Marjorie Patricia George; Cassidy Delaney; Eva Nozik (MDPI AG, 2022)
Pulmonary hypertension (PH) represents a group of disorders characterized by elevated mean pulmonary artery (PA) pressure, progressive right ventricular failure, and often death. Some of the hallmarks of pulmonary hypertension include endothelial dysfunction, intimal and medial proliferation, vasoconstriction, inflammatory infiltration, and in situ thrombosis. The vascular remodeling seen in pulmonary hypertension has been previously linked to the hyperproliferation of PA smooth muscle cells. This excess proliferation of PA smooth muscle cells has recently been associated with changes in metabolism and mitochondrial biology, including changes in glycolysis, redox homeostasis, and mitochondrial quality control. In this review, we summarize the molecular mechanisms that have been reported to contribute to mitochondrial dysfunction, metabolic changes, and redox biology in PH.